2018
DOI: 10.1080/13511610.2018.1497480
|View full text |Cite
|
Sign up to set email alerts
|

Social cohesion revisited: a new definition and how to characterize it

Abstract: This paper provides a general overview on different perspectives and studies on social cohesion, offers a definition of social cohesion that is deeply rooted in current literature, and provides a framework that can be used to characterize social cohesion and help support resilient cities. The framework highlights the factors that play a substantial role in enabling social cohesion, and shows from which perspectives it can be fostered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
173
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(185 citation statements)
references
References 85 publications
(104 reference statements)
0
173
0
12
Order By: Relevance
“…There is still no consensus on how to define values and factors related to the construct of social cohesion. The complexity of the concept of social cohesion can be illustrated by the variety of approaches that can be found in the literature [4,5,7,15,[20][21][22][23][24][25][26][27]. All of them refer, to a varying degree, to six dimensions: social relations, identification, orientation towards the common good, shared values, quality of life, and (in)equality, though it is often indicated that the last three are antecedents or consequences of social cohesion rather than its core dimensions [28].…”
Section: Overview Of Social Cohesion Conceptsmentioning
confidence: 99%
“…There is still no consensus on how to define values and factors related to the construct of social cohesion. The complexity of the concept of social cohesion can be illustrated by the variety of approaches that can be found in the literature [4,5,7,15,[20][21][22][23][24][25][26][27]. All of them refer, to a varying degree, to six dimensions: social relations, identification, orientation towards the common good, shared values, quality of life, and (in)equality, though it is often indicated that the last three are antecedents or consequences of social cohesion rather than its core dimensions [28].…”
Section: Overview Of Social Cohesion Conceptsmentioning
confidence: 99%
“…The key to social cohesion, or 'order against chaos' as Watts (1991) terms it, is to harness psychological constructs in such a manner as to emphasize mutual goals and to de-emphasis contradictory or incompatible aims (Fonscea, Lukosch, & Brazier, 2019). The issue is not merely where the line is drawn at a given point in time, but how certain ideological constructs are elevated or dismissed from discourse in order to facilitate perceived affinities between a dominant group and society at large.…”
Section: American Labor Exceptionalism Through a Durkheimian Lensmentioning
confidence: 99%
“…Under this perspective, the current study focused at the social network analysis approach taking under consideration a set of definitions in well-known social science works, as shown in Table 1. It is worth mentioning that the definitions proposed by the Council of Europe as well as by the Organization for Economic Co-operation and Development (OECD) are considered as the most widely used definitions today [26].…”
Section: Group Cohesion Evaluationmentioning
confidence: 99%